Mortality associated with OsHV-1 in spat Crassostrea gigas: role of wild-caught spat in the horizontal transmission of the disease - Degremont, Lionel; Benabdelmouna, Abdellah (Aquaculture International, 2014)
The French oyster production of Crassostrea gigas is based on two sources of spat: wild-caught (WC) and hatchery-produced (HP). Massive mortality related to the ostreid herpesvirus type 1 (OsHV-1) has affected both sources in France since 2008. We investigated the mortality in juvenile C. gigas due to the horizontal transmission of OsHV-1 within (separated condition) and between (mixed condition) the two spat sources in three environments from April to June 2010. In the separated condition, no mortality was observed in the HP batches, while the WC batches experienced moderate to high mortality (40–80 %). In contrast, the WC and HP batches experienced high mortality in all tested environments for the mixed condition. At the beginning of the trial, the HP batches were all negative for OsHV-1 DNA detection by real-time PCR, while the WC batches were all positive for OsHV-1 DNA detection by real-time PCR, even though the percentage of virus DNA-positive oysters and viral load were low. During the experiment, all batches that exhibited mortality were positive for OsHV-1 with a high viral load, while OsHV-1 was never detected for the HP batches of the separated condition. Together, our results demonstrated that OsHV-1 was horizontally transmitted from the WC oysters to the HP oysters. Our study is the first to indicate that the mortality related to OsHV-1 in HP oysters can be avoided using ponds or tanks. However, these oysters were always protected from OsHV-1, and HP oysters could also experience mortality and spread the disease similar to the WC oysters if such care is not used. Finally, the persistence of OsHV-1 at a sub-clinical level in certain oysters supports the hypothesis that the virus can be reactivated and cause viral replication. The use of the two spat sources is discussed to better understand the spread of the disease among oyster stocks.